UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SDN 17 RUPAT MELALUI SUPERVISI AKADEMIK - Nurmala (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was school action research conducted by the principal. This study aimed to improve the teachers’ performance at SDN 17 X through academic supervision from the principal. The place of research was at SDN 17 X, and the subjects of the research were the teachers who taught at the school. This research used a quantitative descriptive method that described the facts that occurred and found in the field. The results showed that academic supervision improved the teachers’ performance in teaching. It also improved the quality of education and supported the main objectives of learning. It was evident from the data analysis that observed the teachers’ performance during the learning process. The supervision by the principal had a good impact which was seen in the indicator of preparing learning tools and compiling teaching materials getting a score of 3 in the high category, while on the indicator of the ability to open and close the learning the score was 4 in the very high category. Then, the score on the indicator of the ability to carry out the evaluation was 3 in the high category. The score on the ability to use new learning strategies was 3 in the high category. Finally, the score on the indicator of the ability to communicate and build a communicative atmosphere in the classroom was 4 in the very high category. It was proven that the supervision carried out by the principal improved the teachers’ performance in the teaching process.